2012
DOI: 10.5539/mas.v6n2p30
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Bacitracin in Stirred Fermenter by Bacillus Licheniformis Using Defatted Oil Seed Cakes as Substrate

Abstract: Bacitracin is being imported in India involving substantial amount of foreign exchange for its incorporation in poultry feed. The raw material for its production is readily available and cheap such as soybean meal, sunflower meal & wheat bran. Thus development of this technology in this country would result in saving a reasonable amount of foreign exchange by utilizing our resources. The present study is concerned with the biosynthesis of antibioticBacitracin by Bacillus licheniformison laboratory to scale up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…In our study, the optimum temperature for antimicrobial compound production was observed to be 30 to 35 uC. Béahdy (1974) and Haddar et al (2007) observed production of bacitracin and other antibiotics by B. licheniformis (Zarei, 2012) at 37 uC, and it was also seen at 30 uC by Hosny et al (2011).…”
Section: Microbiologysupporting
confidence: 64%
“…In our study, the optimum temperature for antimicrobial compound production was observed to be 30 to 35 uC. Béahdy (1974) and Haddar et al (2007) observed production of bacitracin and other antibiotics by B. licheniformis (Zarei, 2012) at 37 uC, and it was also seen at 30 uC by Hosny et al (2011).…”
Section: Microbiologysupporting
confidence: 64%
“…Sunflower, soybean, and sesame meal were used for the production of clavulanic acid and cephamycin C and by SSF with Bacillus licheniformis for endotoxin and bacitracin. The maximum synthesis of the latter was found in soybean meal [22,[160][161][162].…”
Section: Antibioticsmentioning
confidence: 99%